(untitled) (ETIMA, 2024)
In today’s world, technology surrounds us, and its impact on our daily lives is undeniable. The use of advanced gadgets and software has made our lives easier, thanks to the automation happening around us. The vacuum cleaner has been the last to receive a significant upgrade among the many household appliances. However, the autonomous robotic vacuum cleaner market has seen great success in recent years. This paper aims to explore the complex algorithms powering autonomous robotic vacuum cleaners and make them more understandable. By doing so, this technology will help us to finish our daily tasks more efficiently and with minimal involvement.